An Axial Foilless Diode Guided by Composite Magnetic Field for the Production of Relativistic Electron Beams. (17th February 2021) - Li, Chunxia; Jin, Xiao; Wang, Ganping; Zhang, Beizhen; Gong, Haitao; Gan, Yanqing; Li, Fei; Song, Falun
Abstract : Foilless diode are widely used in high-power microwave devices, but the traditional foilless diodes have large volume, heavy weight, and high power consumption, which are not conducive to the application of high-power microwave system on mobile platform. In order to reduce the size of the foilless diode, improve the transmission efficiency of electron beams, and reduce the weight and power consumption of the guiding magnetic field system, an axial foilless diode with a composite guiding magnetic field system is developed in this paper. By adjusting the structure size and magnetic field parameters of solenoid coil, permanent magnet, and soft magnet, the configuration of the composite magnetic field is optimized. The diameter of the anode tube is about 40% smaller than that of the original structure, and the weight and power consumption of the guiding magnetic system are about 40% lower than that of the original system when the same axial magnetic field intensity in the uniform region is generated. When the magnetic field strength of the permanent magnet is set as 1.4 T and that of the solenoid coil is in the range of 0.5 T∼1 T, the electron beam transmission efficiency is 100%, and the diode impedance is adjustable in the range of 100 Ω∼240 Ω. The experimental results verify the correctness of the simulation analysis. The experimental results show that when the magnetic field strength of the solenoid coil is 0.98 T (0.5 T) and that of the permanent magnet is 1.4 T, the transmission efficiency of the high-current annular electron beam with a peak voltage of 636 kV (590 kV) and a peak current of 3.3 kA (2.6 kA) is 100%, and the diode impedance is about 194 Ω (220 Ω).